Scientific Trend Cartography of Digital Microfinance Research: Mapping Knowledge Evolution and Research Frontiers (2010–2025) - Judijanto, Loso (The Es Economics and Entrepreneurship, 2025)
This study presents a scientific trend cartography of digital microfinance research published between 2010 and 2025, aiming to map the field’s intellectual structure, thematic evolution, and emerging research frontiers. Using a bibliometric research design and data retrieved from the Scopus database, the study applies co-authorship, co-citation, keyword co-occurrence, overlay, and density analyses implemented through VOSviewer. The results reveal that microfinance and financial inclusion form the core knowledge base of the field, while closely interconnected themes such as fintech, digital finance, and digital transformation illustrate the progressive integration of technology into inclusive financial systems. Temporal analysis indicates a clear evolution from early concerns with ICT adoption, literacy, and institutional capacity toward more recent emphases on sustainability, risk assessment, digital platforms, women empowerment, and alignment with the Sustainable Development Goals (SDGs). The findings demonstrate that digital microfinance has matured into a multidisciplinary socio-technical domain embedded within broader development and governance discourses. By visualizing knowledge clusters and research trajectories, this study provides a comprehensive overview of the field’s evolution and offers a forward-looking research agenda to support future theoretical development, policy design, and practice in inclusive digital finance.